EFFECTS OF ZINC, NITROGEN AND VARIABLE TEMPERATURES ON SEEDLING GROWTH OF WHEAT (Biological Sciences - PJSIR, 2002)
4 2 A nutrient culture experiment was conducted to study the effects of Zn (0.0,2.5 and 5.0 mg 1-1, as a source of Zn S0  7H 0),N  (0.0,25  and  50 mg  1-1  as a source of NH  S0 )  and  variable  temperatures  (25° and  28°C) on  seedling  growth    f wheat4        4(cv Mehran-89).  The  leaf  tips  burnt  and  yellowish  green  coloured  leaves  were  observed  irrespective  of  t he treatmentsand temperatures. However, such deficiency symptoms were  prominent  at higher  temperatures  and  at increasing  levels of Zn and N. The shoot and root length and fresh and dry weight of shoot increased on the treatment of 2.5 mg 1-1 Zn alongwith 25 mg 1-1 of N at lower temperature whereas, the fresh and dry weight of root decreased on the similar treatments and temperature . At higher  temperature , the  root and  shoot length  and  their  fresh and  d ry weight  decreased  on  treatments.  It was concluded that at higher  temperature  alongwith  higher  levels of Zn and N, the  seedling growth  decreased , whereas at lower temperature with 2.5, mg 1- 1  of Zn and 25 mg 1-1 N, the growth generally  increased.